2009
DOI: 10.1631/jzus.b0820354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 enrichment on the glucosinolate contents under different nitrogen levels in bolting stem of Chinese kale (Brassica alboglabra L.)

Abstract: Abstract:The effects of CO 2 enrichment on the growth and glucosinolate (GS) concentrations in the bolting stem of Chinese kale (Brassica alboglabra L.) treated with three nitrogen (N) concentrations (5, 10, and 20 mmol/L) were investigated. Height, stem thickness, and dry weights of the total aerial parts, bolting stems, and roots, as well as the root to shoot ratio, significantly increased as CO 2 concentration was elevated from 350 to 800 μl/L at each N concentration. In the edible part of the bolting stem,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 50 publications
(58 reference statements)
1
28
1
1
Order By: Relevance
“…Boomiraj et al (2010) also found that B. juncea was sensitive to changes in CO 2 and temperature. In more recent work on Brassica vegetables, La et al (2009) examined the effects of CO 2 enrichment on the growth of Chinese kale (B. alboglabra) treated with three N concentrations (5, 10 and 20 mmol/L). Height, stem thickness and dry weights of the total aerial parts significantly increased as [CO 2 ] was elevated from 350 to 800 mmol/mol at each N concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boomiraj et al (2010) also found that B. juncea was sensitive to changes in CO 2 and temperature. In more recent work on Brassica vegetables, La et al (2009) examined the effects of CO 2 enrichment on the growth of Chinese kale (B. alboglabra) treated with three N concentrations (5, 10 and 20 mmol/L). Height, stem thickness and dry weights of the total aerial parts significantly increased as [CO 2 ] was elevated from 350 to 800 mmol/mol at each N concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Height, stem thickness and dry weights of the total aerial parts significantly increased as [CO 2 ] was elevated from 350 to 800 mmol/mol at each N concentration. For Chinese kale, results demonstrate that high N supply is also beneficial for growth under higher e[CO 2 ] conditions (La et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Kale is a hardy, cool-season vegetable, similar in use and appearance to broccoli; however, it can be grown year-round in tropical regions because it tolerates summer heat (Noichinda et al, 2007). Epidemiological studies showed that there is a negative relationship between Brassicaceae vegetable intake and the risk of a number of cancers (La et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental conditions for crops growth are controlled and monitored precisely in these facilities (Ryu et al, 2014a,b). Epidemiological studies have suggested that an inverse relationship exists between dietary intake of phytochemicals called glucosinolates in Brassica vegetables and induction of cancer (La et al, 2009). Chinese cabbage is a relatively rich source of a variety of nutrients, and phytochemicals, particularly carotenoids, gluconasturtiin (aromatic glucosinolate), glucobrassicin (indolyl glucosinolate), and progoitrin (aliphatic glucosinolate) (Kang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%